2017
DOI: 10.3390/molecules22071063
|View full text |Cite
|
Sign up to set email alerts
|

Pamidronate-Conjugated Biodegradable Branched Copolyester Carriers: Synthesis and Characterization

Abstract: The need for development of comprehensive therapeutic systems, (e.g., polymer-apatite composites) as a bone substitute material has previously been highlighted in many scientific reports. The aim of this study was to develop a new multifunctional composite based on hydroxyapatite porous granules doped with selenite ions (SeO32−) and a biodegradable branched copolymer-bisphosphonate conjugate as a promising bone substitute material for patients with bone tumours or bone metastasis. A series of biodegradable and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Kido et al [86] used the Comet assay as a final assessment for genotoxicity on tissue samples obtained from rats that were exposed to a ceramic scaffold covered with HA and bioglass; their assays demonstrated the lack of genotoxic effects of the investigated material. Oledzka et al [87] investigated the cyto- and geno-toxicity of a new multifunctional composite based on HA porous granules doped with selenite ions (SeO 3 ) 2− , and their study proved that the investigated materials were non-gentotoxic, as demonstrated by the Umu test (carried out on S. typhimurium TA1535/pSK1002). Yamamura et al used in vivo models for the investigation of biocompatibility, and the lack of cyto- and geno-toxicity in blood, liver, kidney, and lung was noted 30 days after HA implantation [88].…”
Section: Biocompatibility Assessment Of Cap-based Bioceramicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kido et al [86] used the Comet assay as a final assessment for genotoxicity on tissue samples obtained from rats that were exposed to a ceramic scaffold covered with HA and bioglass; their assays demonstrated the lack of genotoxic effects of the investigated material. Oledzka et al [87] investigated the cyto- and geno-toxicity of a new multifunctional composite based on HA porous granules doped with selenite ions (SeO 3 ) 2− , and their study proved that the investigated materials were non-gentotoxic, as demonstrated by the Umu test (carried out on S. typhimurium TA1535/pSK1002). Yamamura et al used in vivo models for the investigation of biocompatibility, and the lack of cyto- and geno-toxicity in blood, liver, kidney, and lung was noted 30 days after HA implantation [88].…”
Section: Biocompatibility Assessment Of Cap-based Bioceramicsmentioning
confidence: 99%
“…Several studies [86,87,88] generally demonstrated, using various models, the lack of genotoxicity of HA-based materials.…”
Section: Biocompatibility Assessment Of Cap-based Bioceramicsmentioning
confidence: 99%
“…Among other filaments, FDM technology allows for additive manufacturing of biopolymers such as lignin and polylactides (PLA), a biodegradable filament used for tissue engineering purposes in various fields of regenerative medicine and dentistry [24][25][26]. Despite environmental advantage in terms of biodegradability, recent studies showed improvements of the mechanical properties by changing the layups of the fibers of subsequent layers [20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, ZOL-loaded bone cement or tricalcium phosphate (TCP) inhibited malignant bone tumors or metastatic bone tumors with the help of sustained ZOL release and acted as a bone substitute at the same time (Koto et al, 2017;Rahmanian et al, 2017). Aliphatic polyesters like PCL, PLA, PLLA were used widely for their good biodegradability, biocompatibility, and permeability (Oledzka et al, 2017). Ewa Oledzka et al prepared a new multifunctional composite as a promising bone substitute material in which HA porous granules doped with selenite ions (SeO 3 2À ) and conjugated biodegradable branched copolymer-BP.…”
Section: Implantable Scaffold or Compositementioning
confidence: 99%